Market‐Based Coordination of Shared Resources in Cyber‐physical Production Sites. Issue 5 (24th April 2017) - Wenzel, Simon; Paulen, Radoslav; Beisheim, Benedikt; Krämer, Stefan; Engell, Sebastian
Abstract: Large interconnected production sites typically consist of many plants that are physically coupled by networks of shared resources. An optimal site‐wide allocation of shared resources is key to a resource‐, energy‐, and cost‐optimal operation. Market‐based coordination can find the site‐wide optimum with limited data exchange between the subsystems and thus ensures confidentiality. In this contribution, market‐based coordination is applied to a simulation study of a petrochemical production site with steam and intermediate products as shared resources. Abstract : Market‐based coordination strategies can balance flows of material and energy in shared‐resource networks between individual autonomous production plants. The distributed approach optimizes energy and resource efficiency by finding the optimal operating point of the site and ensures a high level of confidentiality.